Wound dehiscence after total knee arthroplasty. (2017) - Sazegari, Mohammad Ali; Mirzaee, Fateme; Bahramian, Fateme; Zafarani, Zohreh; Aslani, Hamidreza
Highlights: Any of the wound complications (drainage, hemarthrosis, skin necrosis, and dehiscence) potentially related to diabetes. Wound dehiscence is a complication after total knee arthroplasty especially in diabetic patient. Postoperative care after knee replacement should be more considered in diabetic patients. Abstract: Introduction: Wound dehiscence is one of the most common complications of surgical ulcer, involving the breaking open of the surgical incision along the stitch. This condition is a severe complication of total knee arthroplasty. Presentation of case: We report a case of a 59-year-old female patient with diabetes who underwent a total knee arthroplasty in which all layers of wounds were dehiscence and prosthetic was exposed. Discussion: Wound dehiscence is a complication after total knee arthroplasty especially in diabetic patient. So, patients with diabetes more susceptible to development of wound dehiscence following total knee arthroplasty and should be followed particularly postoperatively care. Conclusion: Postoperative care after knee replacement should be more considered in diabetic patients. Finally the patient was successfully treated with irrigation and debridement (I&D) and polyethylene insert exchange.